PANDANGAN KEAGAMAAN GERE JA BETHANY INDONESIA - Arifuddin Ismail (Balai Penelitian dan Pengembangan Agama Makassar, 2008)
This writing is a conclusion of research, that was conducted in Palu,Central Sulawesi. This writing aims to describe the religious perspectiveofGBI (Gereja Bethany Indonesia), that was considered as a part offundamentalism movement on Christ.The result of study showed that (1) the basic of religious faith of GBI isGod Jesus Christ, and confession that Jesus is messiest, the living Son ofGod. (2) Bible is never wrong. The truth of Bible works at anywhere andanytime. Men have to believe and do what Bible said. (3) Confession toApostle Creed. (4) The church is God institution to realize God in theworld. Church not only means as construction but also means as peopleunited to live in same faith, hope, and love to Jesus Christ. (5) Themovement of GBI emphasis to morality and spirituality especially toyoung generation; (6) their motto is Successful Bethany Family